Constrained Politics: Labour Market Actors, Political Parties and Swedish Labour Immigration Policy. Issue 1 (23rd January 2017) - Boräng, Frida; Cerna, Lucie
Abstract : Sweden used to be one of the most restrictive countries in the Organisation of Economic Development and Cooperation (OECD) in terms of labour immigration policy. This was drastically changed in 2008 when a very liberal immigration law was passed. Why did one of the most restrictive labour immigration countries suddenly become one of the most liberal ones? The article argues that it is necessary to consider labour market institutions and their consequences for labour migration. These factors will influence the preferences, strategies and chances of success for various policy actors. A decline in union power and corporatism in Sweden had important consequences for its labour immigration. Following this decline, employers and centre-right parties became more active and adopted more liberal policy positions than previously. The article analyses policy developments since the 1960s and draws on official documents, position statements, party manifestos, media coverage and original elite interviews.